Optical educational kit - Zheng, Bin (Nanyang Technological University, 2020)
Optics is an important area in physics that studies the properties of the light. There are vari- ous gadgets and inventions in our world that uses the principles of optics. In this project, the aim is to use optical lens to design educational optic kit that can demonstrate the optics prin- ciples. To achieve this objective, various lens with different focal lens will be used and exper- iments will be performed to determine their actual focal lens. Following this, interesting ex- periments will also be designed so that the users can have fun while discovering the princi- ples of optics. The purpose of this report is to document the detailed development process for this project, which includes the experimental designs and performance, challenges faced, and solutions implemented, as well as future recommendations.